Discovery and validation of CREB1 as a transcription target of icaritin: Implications for the treatment of depressive-like behavior - Ling Gu; Lei Li; Huiying Xu; Yuyan Ling; Ruiting Ma; Meijuan Chen (Brain Research Bulletin)
Depression is a prevalent neuropsychiatric disorder characterized by persistent sadness and a lack of interest, significantly impacting the quality of life. Icaritin, a bioactive compound from Herba Epimedii, which has the antidepressant-like effects. However, the potential target of icaritin in the brain, especially concerning transcription factors, is not well understood. In this study, we demonstrated that icaritin significantly ameliorated depressive-like behaviors in a chronic corticosterone (CORT)-induced mouse model. This study aimed to investigate the role of icaritin in modulating the activity of cAMP-response element binding protein 1 (CREB1), a crucial transcription factor implicated in neuronal function and mood regulation. Through a combination of virtual screening and molecular docking, we identified CREB1 as a target by intersections of databases, leading to the selection of 43 candidate compounds, among which icaritin exhibited a favorable docking score and previously reported antidepressant effects. Biolayer interferometry (BLI) analysis confirmed the direct binding of icaritin to CREB1, with a dissociation constant (KD) of 7.02E-06 M. Further mutational analysis revealed that residues Q65 and Q229 of CREB1 were essential for the binding of icaritin. Additionally, Quantitative Real-Time PCR (qRT-PCR) demonstrated that icaritin treatment upregulated the mRNA levels of CREB1 target genes in the hippocampus and cortex. Bioinformatics analysis indicated that CREB1 interacts with several neuroprotective pathways, reinforcing its potential significance in depression. In conclusion, our findings suggest that icaritin may represent a promising therapeutic candidate for depression by enhancing CREB1-mediated neuroprotection, warranting further investigation into its clinical applications and underlying mechanisms.